Recruiting Capable Students to Accounting. - Anderson, Wilton T. (The Accounting Review, 1966)
Abstract The article highlights some attributes required for recruiting superior accounting students. It says that one of the principal problems in the recruitment of capable students to accounting is to identify the students who likely will succeed. Another problem is to inform students and others in an effective manner of the interesting and truthful story associated with opportunities in accounting. Still another problem is to identify and inform people who are influential with capable students, so that these people can counsel and assist their superior students in the selection of a career in accounting. If a person is to succeed in accounting, he must possess a high intellectual capacity. While he must also possess many other attributes, any widely broadcast type of recruitment effort should be directed primarily toward superior students. The efforts described here have been successfully used in recruiting accounting students at Oklahoma State University in Stillwater, Oklahoma. The article discusses various measures taken by the university to recruit accounting students.